Peningkatan Akurasi Umpan Melalui Permainan Target pada Sepak Takraw - Faozi, Faiz; Abdurrahman, Irpan; Pamungkas, Pras Nanda; Bahri, M Syamsul (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study examined the effect of a target-game training model on passing accuracy among extracurricular sepak takraw participants at SMA Negeri 1 Parungkuda. An experimental one-group pretest–posttest design was employed (n = 8). Passing skill was assessed with a standardized test, and data were analyzed using paired-samples t-tests after assumption checks. Results revealed a significant improvement in passing accuracy following the intervention: mean scores increased from 26.75 to 32.62 (a gain of 5.88 points ≈ 22.0%), t(7) = 7.668; p < .001; with a large effect size (d = 2.71). These findings indicate that a well-designed, representative target-game approach is effective for enhancing passing precision in a secondary-school context.